NEUTRONIC ANALYSIS OF THE VVER-1200 LATTICE CELL FUEL USING WIMSD-5B CODE - Santo Paulus Rajagukguk; Syaiful Bakhri; Ana Muliyana; Juniastel Rajagukguk (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2022)
The calculation of safety parameters in nuclear reactors has an important influence on nuclear reactor control and safety. The infinite multiplication factor, reactivity coefficients, and power peaking factor parameters are the most important safety parameters for determining reactor status. The aim of the present study is to analyze the behavior of the nuclear safety parameters for the VVER-1200 core in a normal state of reactor operation. A lattice cell fuel model of the VVER-1200 reactor core was performed using WIMSD-5B. The cross-section library data based on the ENDF/B-VIII.0 was used. The investigated parameters were the value of infinite multiplication factor with different pitch, temperature, enrichment, and boron concentration.Â  The calculation also investigated the reactivity coefficient parameters. The verification of WIMS model VVER-1200 was performed by comparing the results of the WIMSD-5B code with VVER-1200 data in the SAR document, and it was implied that they are in good agreement. The calculated values of reactivity coefficients illustrated a safe behavior.